Character displacement drives floral variation in Pelargonium (Geraniaceae) communities. (9th January 2020) - Newman, Ethan; Anderson, Bruce
Abstract: Interactions between plant community members are an underexplored driver of angiosperm floral variation. We investigate character displacement as a potential contributor to floral variation in Pelargonium communities. Pelargoniums all place pollen on the ventral sides of their pollinators, potentially leading to interspecific pollen transfer (IPT) in sympatry. We show that the positions of pollen placement and receipt are determined by anther and style exsertion lengths. Using field experiments, we demonstrate that heterospecific species experience higher IPT if they have similar style lengths than when they have greater style length differences. Using crosses, we show that IPT has negative consequences on seed set. In combination, these results suggest that character displacement in style length is likely to reduce IPT and increase female fitness in sympatry. Patterns of style length variation across 29 different Pelargonium communities suggest that character displacement has occurred in multiple communities. Furthermore, analyses using a wide‐ranging species pair show that style lengths are more different between sympatric populations than they are between allopatric populations. In addition to pollinators as agents of floral divergence, this study suggests that variation in Pelargonium community structure has driven style length variation through character displacement.